Decision support systems and academic networks as a support for academic decisions - Çankaya, Nevzat (My University, 1991)
unknown
Keywords: BİLGİ AĞLARI; Şirketler - KARAR VERME; Şirketler-BİLGİ AKIŞ SİSTEMİ